Kaempferol Protects Blood Vessels From Damage Induced by Oxidative Stress and Inflammation in Association With the Nrf2/HO-1 Signaling Pathway - Yao, He; Sun, Jingyu; Wei, Jie; Zhang, Xin; Chen, Bing; Lin, Yajun (Frontiers in Pharmacology, 2020)
Over recent years, an increasing number of studies have confirmed that the occurrence and development of vascular pathological changes are closely related to oxidative stress and the inflammatory response of the vascular endothelium. Kaempferol is the most common flavonoid compound found in fruits and vegetables. Our present research identified that kaempferol had the capability to protect the vascular endothelium in a mouse model of vascular injury and explored the specific mechanisms underlying these effects by investigating oxidative stress, the extent of cardiovascular injury, and inflammatory markers such as NF-κB, TNF-α, IL-6, and the Nrf2/HO-1 signaling pathway. Analysis showed that kaempferol reduced oxidative stress and inflammation mediated by H2O2 and paraquat, respectively, both in vitro and in vivo. Furthermore, kaempferol suppressed the levels of TNF-α and IL-6, and the activation of NF-κB, in aortic tissues and human umbilical vein endothelial cells (HUVECs). Finally, we observed that kaempferol corrected the levels of antioxidants and elevated the protein levels of Nrf2 and HO-1 in aortic tissues and HUVECs. Collectively, our findings prove that kaempferol protects blood vessels from damage induced by oxidative stress and inflammation and that the Nrf2/HO-1 signaling pathway plays a key role in mediating these effects.